2005
DOI: 10.1017/s1473550405002727
|View full text |Cite
|
Sign up to set email alerts
|

Hypobaric bacteriology: growth, cytoplasmic membrane polarization and total cellular fatty acids in Escherichia coli and Bacillus subtilis

Abstract: Escherichia coli JM109 (Gram-negative) and Bacillus subtilis (Gram-positive) were grown under hypobaric conditions for 19 days at 25 °C to study the effects of 33 and 67 kPa low pressures on selected physiological responses; growth, cytoplasmic membrane polarization (measure of cytoplasmic membrane fluidity) and total cellular fatty acids. In the first experiment, cytoplasmic membrane polarization in B. subtilis increased under both hypobaric conditions, indicating the membrane became more rigid or less fluid.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Three recent papers (Kanervo et al, 2005;Pokorny et al, 2006;Sakon and Burnap, 2006) examined microbial growth at pressures below an Earth-standard sea level pressure of 1013 mbar, but pressures were still much higher ( > 100 mbar) than those found on Mars (datum pressure = 6.1 mbar). reported that germination and subsequent growth were arrested at 35 mbar for endospores of seven Bacillus spp., while log-phase vegetative cells of several species were capable of minimal, but observable, growth down to 25 mbar.…”
Section: Introductionmentioning
confidence: 99%
“…Three recent papers (Kanervo et al, 2005;Pokorny et al, 2006;Sakon and Burnap, 2006) examined microbial growth at pressures below an Earth-standard sea level pressure of 1013 mbar, but pressures were still much higher ( > 100 mbar) than those found on Mars (datum pressure = 6.1 mbar). reported that germination and subsequent growth were arrested at 35 mbar for endospores of seven Bacillus spp., while log-phase vegetative cells of several species were capable of minimal, but observable, growth down to 25 mbar.…”
Section: Introductionmentioning
confidence: 99%
“…As stated previously, the known biosphere is contained within the troposphere, where the lowpressure limit is ϳ10 kPa (62). Interestingly, this is also the lower limit of pressure before significant decreases in growth rate and colony size were demonstrated in a number of Gram-positive and Gram-negative bacterial species (10,11,29,31). Therefore, it appears for most bacteria (with a few notable recent exceptions mentioned above [10,11]) that there exists a low-pressure limit at ϳ10 kPa, below which cellular processes begin to be inhibited and the GSR is induced in B. subtilis.…”
Section: Resultsmentioning
confidence: 65%
“…To date, several bacterial species have been tested for growth and/or metabolism under various LP regimes (28)(29)(30)(31). In most species tested, growth was observed to be essentially normal from ϳ101 kPa down to 10 kPa, but the growth of most microorgan-isms slowed dramatically at pressures below 10 kPa and essentially ceased at 2.5 kPa (11,31).…”
mentioning
confidence: 99%
“…Mostly, these studies have limited the lowest pressure tested to 25 mbar, presumably to prevent excessive water evaporation. Results have often been comparable to those performed on agar, in that low pressure inhibits and slows growth; or the effect is bacteriostatic, and bacteria are able to resume growth at atmospheric pressure (Kanervo et al, 2005;Pokorny et al, 2005;Schuerger et al, , 2013. Nevertheless, Berry et al (2010) showed that growth is unaffected in both a strain of Escherichia coli (ATCC 35218) and Serratia liquefaciens (ATCC 7592) when pressure is reduced to 25 mbar, and Schuerger et al (2013) went on to show that S. liquefaciens can survive and grow under Mars-like conditions of 0°C, a CO 2 -enriched atmosphere, and at a pressure of 7 mbar.…”
Section: Biological Stressmentioning
confidence: 98%